Total coliform dalam Air Bersih dan Escherichia coli dalam Air Minum pada Depot Air Minum Isi Ulang - Sekarwati, Novita; Subagiyono, Subagiyono; Wulandari, Hanifah (Universitas Ahmad Dahlan, 2016)
Background: Refill drinking water station are industrial that perform processing raw water into drinking water and sell directly to consumers. It caused Coliform bacteria in the water would be infectious. Escherecia coli bacteria in drinking water have provisions 0/100 ml. The potentially pathogenic of the bacteria in certain circumstances can cause diarrhea.The purpose of this study was to determine the number of Total coliform Bacteria and Escherechia coli in Drinking Water at Refill Water Station in Kalasan, Yogyakarta. Method: This research was descriptiveÂ with laboratory test.The population of this study was 8 refill water station in Kalasan. This research used checklist to determine the physical condition and laboratory test to determine the number of total coliform and Escherecia coli in the water. Results: The results of this study showed that influence the number of bacteria is the source of water, filter tubes, pumping equipment, operator or employee hygiene, the low qualification of micro filter and inadequate the facilities, There were seven water refill station which the number of bacteria upper than standard.Conclusion: All of the refill water station unmeet the standard of drinking water.